Simultaneous Detection of Homocysteine and Cysteine in the Presence of Ascorbic Acid and Glutathione Using a Nanocarbon Modified Electrode - Lee, P; Lowinsohn, D; Compton, R (Wiley, 2014)
The simultaneous electrochemical detection of homocysteine and cysteine using an absorbed ortho-quinone species, catechol, at the nanocarbon modified glassy carbon electrode was achieved via 1,4-Michael addition reaction. The detection was done in the presence and the absence of each other as well as with both glutathione and ascorbic acid present in order to investigate the selectivity of homocysteine and cysteine. A determination of homocysteine sensitivity is (0.882±0.296)nAnM-1 with a LOD of ca. 11nM and cysteine sensitivity is (7.501±0.202)mAμM-1 with a LOD of ca. 5.0μM within a range of 0-0.1mM. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.